Projeto de um vagão gondola em alumínio para o transporte de minério - Almeida, Murilo Vasques Thibau de (1989)
This text describes the design of a gondola car in aluminum using modern computer technics. This wagon aims to the transportation of ore and uses aluminum alloys capable to obtain less weight in its structure comparatively to a similar wagon in steel. There are in this work a general description of freight car types, the criterion used in the three-dimensional modelling for the gondola car, the considerations about the applied loads on the element during the structural analyses, and the checking of tension levels over the cross-section of each member.